Risks to the Fetus of Anticoagulant Therapy During Pregnancy - Ginsberg, Jeffrey S; Hirsh, Jack; Turner, D Christoper; Levine, Mark N; Burrows, Robert (Thrombosis and Haemostasis, 1989)
The use of anticoagulants during pregnancy is problematic because of the potential adverse effects to the mother and the fetus. Heparin does not cross the placenta, and thus, it was surprising that a recent report concluded that heparin therapy during pregnancy was as risky as oral anticoagulant therapy. Therefore, we performed a literature review of fetal/infant outcomes following anticoagulant therapy during pregnancy. We examined 186 reports which described fetal/infant outcomes in 1,325 pregnancies associated with anticoagulant therapy. The rates of adverse fetal/infant outcomes including death, prematurity and congenital malformations following treatment with heparin, oral anticoagulants, or both were calculated. The previously described high rate of adverse feta/infant outcomes with heparin- treated patients, could be accounted for by the frequent use of heparin in pregnancies with comorbid conditions independently associated with adverse outcomes and by reports of uncomplicated prematurity. After excluding such pregnancies, outcomes in heparin-treated patients are similar to the normal population.
Keywords: Pregnancy; Heparin; Oral anticoagulants; Thromboembolism